STUDI PENGGUNAAN PENYEARAH 18 PULSA DENGAN TRANSFORMATOR 3 FASA KE 9 FASA HUBUNGAN SEGIENAM - Ahmad Saudi Samosir (Universitas Ahmad Dahlan, 2008)
The 18-pulse converter, using Y or D-connected differential autotransformer, is very interesting since it allows natural high power factor correction. The lowest input current harmonic components are the 17th and 19th. The Transformer is designed to feed three six-pulse bridge rectifiers displaced in phase by 200. This paper present a high power factor three-phase rectifier bases on 3-phase to 9-phase transformer and 18-pulse rectifier. The 9-phase polygon-connected transformer followed by 18-pulse diode rectifiers ensures the fundamental concept of natural power factor correction. Simulation results to verify the proposed concept are shown in this paper.